Peranan Manajemen Sekuriti Dalam Mengamankan Dan Memecahkan Masalah PT SK Keris Indonesia - Edy Soesanto; Alifah Jiddal Masyruroh; Ganis Aliefiani Mulya Putri; Srirahayu Putri Maharani (Lembaga Pengembangan Kinerja Dosen, 2023)
PT SK Keris Indonesia is a joint venture company operating in Indonesia and is part of SK Chemicals' global strategy. This company produces various types of products, such as polyester filament yarn, PET resin for bottles, PET film, as well as several specialty chemicals that are tailored to orders from consumers. Given the types of products produced and the large size of the company, security at PT SK Keris Indonesia is very important. This study was made to find a correlation between the role of security management and security breaches. The results of the study show that the Security Unit at PT SK Keris has not optimally and coordinatedly utilized all parties related to the security of PT. SK Keris including the local police. SK Keris, needs to take advantage of the potential that exists from within and around it, including by building cooperation with the local police apparatus.